Antibody drug conjugates targeting HER2: Clinical development in metastatic breast cancer. (December 2022) - Rassy, Elie; Rached, Layal; Pistilli, Barbara
Abstract: The identification of the HER2 alteration as an actionable oncogenic driver in breast cancer has propelled the development of HER-targeting monoclonal antibodies (mAb) such as trastuzumab and pertuzumab, which led to dramatic improvements in survival outcomes. Lately, the great strides made toward developing antibody-conjugation methods have led to the development of a new class of compelling compounds, the antibody-drug conjugates (ADCs) targeting HER2 which have profoundly transformed the treatment landscape of breast cancer. HER2-targeting ADCs, trastuzumab-emtansine and trastuzumab-deruxtecan, have improved the overall survival in the second and third-line settings with manageable adverse events. Other HER2-targeting ADCs using novel technological advances in the antibody, linker and/or payload conception have shown promising activity in preclinical and clinical studies and some of them are now being evaluated in larger clinical trials. Multiple challenges still impede the success of ADCs in breast cancer namely the lack of a comprehensive understanding of resistance mechanisms as well as the mechanisms of action of ADCs in special subgroups of patients such as those with low or ultra-low HER2 expression and patients with brain or leptomeningeal metastases (BM). In this framework, we review the approved indications and ongoing trials for HER2-targeting ADCs, across patient subgroups, including those with BM and discuss the associated potential mechanisms of action and resistance. Last, we provide an overview of the future perspectives involving HER2-targeting ADCs in breast cancer. Highlights: HER2 targeting ADCs have changed the treatment landscape of metastatic HER2+ BC. The third generation HER2 targeting ADC, T-DXd, is effective against HER2-low/ultralow BC. The validation of new techniques to refine the definition of HER2 expression is required. Ongoing translational research aims to evaluate the mechanisms of action and resistance to this new generation of ADC's. Current clinical trials aim to evaluate treatment combinations and new HER2-tagreting ADCs.